THEORY OF PLANNED BEHAVIOR APPLICATION ON MOTORCYCLE RIDER SAFETY BEHAVIOR - Jalaludin, Jalaludin; Widyaningsih, Nunung; Dwiatmoko, Hermanto (ASTONJADRO, 2021)
In Indonesia, the basis for implementing road safety consists of five pillars which are compiled in the General National Road Safety Plan (RUNK). One of the pillars proclaimed is the behavior of safe road users. This aims as an effort to reduce traffic accidents because road users are the biggest factor in road accidents related to user behavior. The cases of road traffic accidents in Indonesia are dominated by motorcyclists, especially Jakarta, which is one of the cities with a fairly high rate of motorcycle accidents. Because the behavior of road users is closely related to traffic accidents, and also motorcyclists are the users who are involved in the highest traffic accidents, this study explains the factors that determine the safety behavior of motorcyclists in Jakarta. The application of the Theory of Planned Behavior (TPB) is used as a basis for finding the factors that may determine the behavior of the motorcyclist. Furthermore, the research approach used in this study is quantitative with primary data in the form of a closed questionnaire instrument from 230 respondents who ride motorcycles in Jakarta. The data analysis technique used is the Structural Equation Modeling (SEM) approach using the AMOS 22.00 program as a tool in determining the determinants of driver safety behavior. The results of the analysis show that the most dominant direct predictor in determining the safety behavior of motorcyclists in Jakarta is the intention to behave safely. While the indirect factor that determines is the attitude of the driver. The results of the analysis also show that the age of the driver has a significant influence on safety behavior.